High Levels of Soluble P-selectin, Neutrophil Extracellular Traps, and Myeloperoxidase as Risk Factor of Deep Vein Thrombosis in Malignancy Patients Receiving Platinum-Based Chemotherapy [version 2; peer review: 2 approved, 1 approved with reservations] - Ketut Suega; I Made Bakta; Ni Made Renny Anggreni Rena (F1000Research)
Backgrounds Venous Thromboembolism (VTE) is a disease entity comprising Deep Vein Thrombosis (DVT) and Pulmonary Embolism (PE). VTE events increase the mortality rate of patients with cancer receiving platinum-based chemotherapy. Soluble P-Selectin, Neutrophil Extracellular Traps (NET), and myeloperoxidase (MPO) are risk factors associated with DVT in malignancy patients receiving platinum-based chemotherapy. The purpose of this study was to determine the role of soluble P-selectin, NET, and MPO as risk factors for DVT in patients with malignancy receiving platinum-based chemotherapy. Patients and Methods This study used a case-control design (matched pair case-control study) based on age and gender. The case group consisted of subjects with DVT, whereas the control group consisted of subjects without DVT. The subjects were 31 in each case and control groups. Soluble P-selectin, NET, and MPO levels were measured in each group. Results The mean age of case group was 50.26±12.15 years meanwhile in control group was 52.81±11.64 years. In the case group, 71% of the subjects were female, whereas 51.6% of the control group were male. Most subjects, either in the case group (71%) or the control group (71%), used carboplatin. In the case group, cervix malignancy was the most common malignancy (32.3%), whereas in the control group, it was nasopharyngeal malignancy (25.8%). High soluble P-selectin level was a risk factor for DVT (OR 3.38, CI 1.180 – 9.780, p=0.02). A high NET level was also a risk factor for DVT (OR 2.88, CI 1.026-8.074, p=0.04). The high MPO levels in this study could not be proven as a risk factor. Conclusions Soluble P-selectin and NET are risk factors that play a role in the pathophysiology of DVT through the pathomechanism of immunothrombosis induced by endothelial injury and activation of monocytes and neutrophils due to the use of platinum-based chemotherapy.